The meaning of the Ceprotan tradition in bersih desa for the people of Sekar village - Laras Andita Yuningtyas; Sigit Pranawa; Yuhastina Yuhastina (Harmoni Sosial: Jurnal Pendidikan IPS, 2020)
The purifying tradition carried out by the Sekar Village community is always accompanied by a traditional ceremony called Ceprotan. This Ceprotan traditional ceremony only exists in Sekar Village. Its implementation load with folklore values that the local people believe. This study aimed to know the meaning of the Ceprotan tradition for the people of Sekar village. This research used a qualitative method with a phenomenological approach. The intake of informants was done through the purposive sampling technique. Data obtained using both secondary and polymer data. Data collection techniques used were interviews, observation, and documentation. To ensure the validity of the data, the researcher used source triangulation techniques on the data obtained. The data were then analyzed with cultural interpretation techniques or the "thick description" approach by Clifford Geertz to interpret the symbol systems of cultural meaning in a deep painting. This study's findings were that the village's purifying tradition accompanied by the Ceprotan traditional ceremony carried out by the Sekar Village community, especially Krajan Lor and Krajan Kidul Hamlets, was done as an expression of gratitude, hope, and prayer to God Almighty for good things. Based on cultural practitioners' symbolic activities that appeared and were interpreted, this tradition was also carried out as a form of appreciation and reminder to the ancestors of Sekar Village, which until now is believed by the community as Danyang who consider influencing the survival of the local people. This belief contains in the folklore of the origin of Sekar Village. It continues to maintain as a form of refinement of the customs and culture of Sekar Village.